Perencanaan Sistem Penyediaan Air Bersih dengan Metode Treatment di Desa Sidogede Kecamatan Prembun Kabupaten Kebumen dalam Program Pamsimas III 2021 - Intansari, Dyah Widi Astin; Susanto, Ari (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The supply of clean water for the residents of Sidogede Village, Prembun District, is currently insufficient. In order to be able to obtain water for their daily needs, some people still transport it. The need for clean water in some places does not match the amount of clean water available in that place, so that it does not meet the demand for water. Around this area there is a river flow which has the potential to be utilized for planning the supply of clean water. Population growth for this village is calculated by projecting water demand. Plan year on the water supply system for the next 15 years from 2021. In this study, four units of parallel dug wells were used for extraction. The clean water supply system includes raw water intake, reservoir, processing, and distribution systems in providing clean water. The distribution of clean water to service locations uses a gravity system with a simple water treatment system with a 3m x 2m x 2m reservoir to store water and become one building with a treatment tub. The clean water treatment design uses treatment processing which contains zeloid stones. The design of a clean water supply system uses hydraulic calculations for pipe dimensions. The use of infiltration wells with pumps is channeled to the Treatment Tub and to the Reservoir and then channeled to the service area using PVC pipes. The diameter for the transmission pipe is 1.5'' and for the distribution pipe is 1''. Keyword: distribution, treatment, hydraulics, pipes, reservoirs